2001
DOI: 10.1088/0954-0083/13/4/311
|View full text |Cite
|
Sign up to set email alerts
|

Surface Contamination of Some Materials of the Space Station ‘MIR’

Abstract: About 60 samples of various materials exposed to low Earth orbit (LEO) conditions for 997 days on board the orbital space station ‘Mir’ were investigated. The aim was to determine the properties of the contamination layers formed during LEO exposition. The following methods were used: optical and scanning electron microscopy, local x-ray microanalysis, secondary ion mass spectrometry in fast atom bombardment ionization mode, electron spectroscopy for chemical analysis, temperature programmed desorption mass s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Indeed, alpha-line of Lyman series of atomic hydrogen (121.6 nm; photon energy 10.7 eV) dominates in the spectrum of Solar VUV radiation. Moreover, radiation with wavelength 121.6 nm induces photoionization of macromolecules with their subsequent transformations similar to those induced by other types of ionizing radiations (Dorofeev & Skurat 1982; Barbashev et al 1992; Skurat & Dorofeev 1994; Van Eesbeek et al 1994; Skurat et al 1997; Skurat et al 2001; Skurat & Samsonov 2001; Skurat 2003). However, a substantial difference of absorbed radiation doses is observed in gamma-radiolysis, bombardment by fast electrons and VUV irradiation (see, for example, (Skurat 2003)).…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Indeed, alpha-line of Lyman series of atomic hydrogen (121.6 nm; photon energy 10.7 eV) dominates in the spectrum of Solar VUV radiation. Moreover, radiation with wavelength 121.6 nm induces photoionization of macromolecules with their subsequent transformations similar to those induced by other types of ionizing radiations (Dorofeev & Skurat 1982; Barbashev et al 1992; Skurat & Dorofeev 1994; Van Eesbeek et al 1994; Skurat et al 1997; Skurat et al 2001; Skurat & Samsonov 2001; Skurat 2003). However, a substantial difference of absorbed radiation doses is observed in gamma-radiolysis, bombardment by fast electrons and VUV irradiation (see, for example, (Skurat 2003)).…”
mentioning
confidence: 88%
“…Previous studies demonstrated that, main components of contaminating deposits on outer surfaces of orbital stations contain the chemical groups SiO x ( x ≤ 2) and carbon-containing groups (identified by X-ray photoelectron spectroscopy (XPS)) formed from volatile organosilicone compounds of intrinsic outer atmosphere (Skurat et al . 2001, 2011, 2013). Their origin and chemical composition are not completely understood and therefore are the objects of research.…”
mentioning
confidence: 99%
“…Sun et al, 53 in a contribution to heterogeneous catalysis, used XRMF to measure the adsorption of metal salts by porous gamma-alumina beads. Skurat et al 54 examined about 60 samples from the space station 'MIR' to assess the degree of surface contamination that had occurred in low Earth orbit. X-ray microfluorescence was one of a number of techniques used to assess surface contamination and substrate erosion of the various materials by particles comprised predominantly of Si, with Ca and K. In another materials characterisation application, Istratov et al 55 reviewed the advantages and limitations of a number of novel and emerging techniques used to understand phenomena and defects that limit the lifetime of solar cells.…”
Section: X-ray Optics and Microfluorescencementioning
confidence: 99%